Cocaine Effects on Dopaminergic Transmission Depend on a Balance between Sigma-1 and Sigma-2 Receptor Expression - Aguinaga, David; Medrano, Mireia; Vega-Quiroga, Ignacio; Gysling, Katia; Canela, Enric I.; Navarro, Gemma; Franco, Rafael (Frontiers in Molecular Neuroscience, 2018)
Sigma 1 and 2 receptors are targets of cocaine. Despite sharing a similar name, the two receptors are structurally unrelated and their physiological role is unknown. Cocaine increases the level of dopamine, a key neurotransmitter in CNS motor control and reward areas. While the drug also affects dopaminergic signaling by allosteric modulations exerted by 1R interacting with dopamine D1 and D2 receptors, the potential regulation of dopaminergic transmission by 2R is also unknown. We here demonstrate that 2R may form heteroreceptor complexes with D1 but not with D2 receptors. Remarkably 1, 2 and D1 receptors may form heterotrimers with particular signaling properties. Determination of cAMP levels, MAP kinase activation and label-free assays demonstrate allosteric interactions within the trimer. Importantly, the presence of 2R induces bias in signal transduction as 2R ligands increase cAMP signaling whereas reduce MAP kinase activation. These effects, which are opposite to those exerted via 1R, suggest that the D1 receptor-mediated signaling depends on the degree of trimer formation and the differential balance of sigma receptor and heteroreceptor expression in acute versus chronic cocaine consumption. Although the physiological role is unknown, the heteroreceptor complex formed by 1, 2 and D1 receptors arise as relevant to convey the cocaine actions on motor control and reward circuits and as a key factor in acquisition of the addictive habit.